Cost-effectiveness of club-foot treatment in low-income and middle-income countries by the Ponseti method - Grimes, C; Holmer, H; Maraka, J; Ayana, B; Hansen, L; Lavy, C (BMJ Publishing Group, 2016)
Background Club foot is a common congenital deformity affecting 150 000–200 000 children every year. Untreated patients end up walking on the side or back of the affected foot, with severe social and economic consequences. Club foot is highly treatable by the Ponseti method, a non-invasive technique that has been described as highly suitable for use in resource-limited settings. To date, there has been no evaluation of its cost-effectiveness ratio, defined as the cost of averting one disability-adjusted life year (DALY), a composite measure of the impact of premature death and disability. In this study, we aimed to calculate the average cost-effectiveness ratio of the Ponseti method for correcting club foot in sub-Saharan Africa. Methods Using data from 12 sub-Saharan African countries provided by the international non-profit organisation CURE Clubfoot, which implements several Ponseti treatment programmes around the world, we estimated the average cost of the point-of-care treatment for club foot in these countries. We divided the cost of treatment with the average number of DALYs that can be averted by the Ponseti treatment, assuming treatment is successful in 90% of patients. Results We found the average cost of the Ponseti treatment to be US$167 per patient. The average number of DALYs averted was 7.42, yielding a cost-effectiveness ratio of US$22.46 per DALY averted. To test the robustness of our calculation different variables were used and these yielded a cost range of US$5.28–29.75. This is less than a tenth of the cost of many other treatment modalities used in resource-poor settings today. Conclusions The Ponseti method for the treatment of club foot is cost-effective and practical in a low-income country setting. These findings could be used to raise the priority for implementing Ponseti treatment in areas where patients are still lacking access to the life-changing intervention.